Improvement of Uniform Oil Displacement Technology on the Example of Kazakhstani Fields - ZHUMADILULI, Abdeli D.; PANFILOV, Irina V.; ISMAILOVA, Jamilyam A. (Journal of Environmental Management and Tourism; Vol 9 No 3 (2018): JEMT Volume IX Issue 3(27) Summer 2018, 2018)
Most of oil companies today are focused on increasing the recovery factor from their oil fields. New drilling and well technologies as well as last advances in reservoir management, monitoring and Enhanced Oil Recovery (EOR) methods are thought to play a major role to meet the future demand of energy. Current decline in discovery of new oilfields intensified by a decline in oil prices make industrial companies to work on development of new efficient and economic techniques that will allow better production at lower cost. One such technology developed at Kazakh National Research University is presented in this paper. The latter propose the use of specific perforated holes on tubing liners in order to control the rate of water injection into variably permeable layers and to prevent non-uniform displacement of oil. The study was initially conducted on experimental facility that proved a positive correlation between the perforation density and water flow rates. Then the simulation test was performed using the data from several Kazakhstani oil fields. The results show an increase of sweep efficiency as well as a decrease in water-cut compared to traditional well case.